Patterns, trends and policy implications of private spending on skills development in Mexico and the United States - Miguel Székely; Pamela Mendoza (Inter-American Development Bank (IDB), 2017)
This paper explores families' investment in skills development through education in a high-inequality, low-education quality country such as Mexico, comparing it to a lower-inequality, higher-quality education country such as the United States. The paper uses a series of high-quality Household Income and Expenditure Surveys for both countries spanning around 20 years and different methodological approaches. Of particular interest is the analysis of education expenditure patterns along the income distribution. Policy implications for both cases are discussed. While in Mexico stimulating private spending in education through public resources might be regressive, the opposite might be the case in the United States.
Keywords: D1; I2; J21; 330; Education; Inequality; Private spending; Skills formation